Légitimité littéraire de la littérature jeunesse : les Hunger Games de Suzanne Collins - Sechin, Anne (Romanica Silesiana, 2021)
The Hunger Games trilogy, an international commercial success, enables us to question the relationship between sales records and literary quality as well as to think critically about the literary status of Young Adult Literature. Are there some objective criteria that make it possible to establish a literary status, and can they be applied to Young Adult literature, especially as those works are usually perceived as “popular culture”?